(untitled) - Weakland, Mark; Cornia, Christian - illustrator; Warner Bros. (North Mankato, Minnesota, 2014)
"Uses popular cartoon character Wile E. Coyote to demonstrate science concepts involved with forces and motion"--Provided by publisher."--
Includes bibliographical references and index.
Ages 10-12.
Grades 4 to 6.
Accelerated Reader AR
Keywords: Experiments; Juvenile literature; Wile E. Coyote (Fictitious character); Juvenile literature; Science projects; Juvenile literature; Juvenile literature; Experiments; Juvenile literature; Kinematics; Kinematics; Force and energy